Microstructural changes in soils induced by wetting and drying: Effects on atrazine mobility. (3rd February 2019) - Dor, Maoz; Emmanuel, Simon; Brumfeld, Vlad; Levy, Guy J.; Mishael, Yael G.
Abstract: Wetting and drying affects soil structure and pesticide migration, which both may lead to land degradation. The effect on soil structure has been mainly addressed by classical methods at the macroaggregate scale, and the effect on herbicide leaching has not been thoroughly addressed. We aimed to characterize the effects of wetting and drying on soil microstructure, aggregate packing and stability, and subsequent effect on pesticide mobility in three agricultural soils. We developed advanced methods to quantitatively describe soil microstructure changes, induced by wetting and drying. Changes in soil packing, observed by micro‐CT, indicate that large aggregates in a Clay soil disintegrate, whereas particles from a Sandy Loam form larger aggregates. To reflect these changes in terms of soil stability, we developed an aggregate durability index, based on changes in soil particle‐size distribution measured by laser granulometry. For a Clay soil, the index decreased from 17.0% to 1.7%, indicating soil disaggregation upon wetting and drying. Whereas for a Sandy Clay Loam soil, the index increased from 0.4% to 2.6%, indicating formation of more durable aggregates, explained in terms of cementation by CaCO3 . As expected, wetting and drying did not alter a Loamy Sand soil structure. The adverse effects of wetting and drying on soil structure correspond with the trends of atrazine mobility. As atrazine is trapped within the Clay soil aggregates, disaggregation leads to a 35% enhancement in pesticide mobility, whereas stabilization of a Sandy Clay Loam aggregates reduced atrazine leaching by 23%. Finally, wetting and drying directly affects the soil microstructure, which has an immense indirect effect on pollutant mobility, with both potentially leading to land degradation.